New Methods of Designing the Balanced Scorecard Method for Management in Industrial Companies - Roman Kozel; Milan Mikolas; Sarka Vilamova; Petr Ocko (Communications - Scientific letters of the University of Zilina, 2017)
The Balanced Scorecard (BSC) is a strategic performance measurement system for enterprises, which allows managers of industrial corporations to measure variables that are based on strategic goals of a company. The issue while creating and implementing the BSC system could lay in a mere copying of its traditional forms without incorporating specific needs of a particular enterprise. This article aims to present the research results of a team of authors that was, in cooperation with managers of selected companies in the Moravian-Silesian region, searching for an answer to a question, whether it is possible to simplify the creation process of the BSC without losing the information value of the whole method or of its individual parts. At the same time it was examined whether, in the case of heavy industry, there are different priorities against others.